(3GdEYdGe HhajGJ GdCYdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3bWH GdOjf eMeO Hf eMeO Hf GdNjVQi s)
(3ChdgG (B:s
(3GdMeO ddg CbUi GdMeO hefJgGg , hGdUdGI hGdSdGe Ydi eMeO fHjg heUWaGg gPg JPcQg ddMGaX ai hajGJ GdCYdGe GdSfg GdChdi ef GdgLQI , GdfbjHGf CSYO Hf RGOg s
(3BNQgG (B:s
(3SYjO GdMQjQi hGHf fjQeI hHNGdO hYbjd GdCMdL Hf YHOGddg hESeGYjd Hf CHj NdO s
(3eQJH Ydi GdWHbGJ ef Ghd GdgLQIs
(3Ydi WHbI YTQ Sfjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B48 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B23 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs